Key Drivers for a successful NPD launch strategy - Padwal, Smita (2009)
The successful factors in new product strategy are identified. Product acceptance, the role of brand equity and pricing policy are particularly delved into. The importance of open innovation, outsourcing and networks in the new product development process is also discussed. Extensive literature around the new product development process and strategy is reviewed. Consumer research with regards to product acceptance, price and brand equity is also carried out. Thus finally the key drivers to a successful launch are identified.